2019
DOI: 10.1093/pubmed/fdz053
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of Severe Acute Respiratory Infection (SARI) Cases at a sentinel site in Egypt, 2013–15

Abstract: A B S T R A C TBackground Sentinel surveillance for severe acute respiratory infection (SARI) in Egypt began in 2006 and occurs at eight sites. Avian influenza is endemic, and human cases of influenza A (H5N1) have been reported annually since 2006. This study aimed to describe the epidemiology of SARI at a major sentinel site in the country.Methods Data included in the study were collected from a major SARI sentinel site in Egypt during three consecutive years .Results A total of 1254 SARI patients conforming… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…Severe acute respiratory infection (SARI) has been considered an important contributor to morbidity and mortality in all age groups, particularly children, elderly individuals and individuals with compromised immune, cardiac and pulmonary systems, worldwide [1][2][3]. It is estimated that SARI causes approximately 4.2 million deaths annually.…”
Section: Introductionmentioning
confidence: 99%
“…Severe acute respiratory infection (SARI) has been considered an important contributor to morbidity and mortality in all age groups, particularly children, elderly individuals and individuals with compromised immune, cardiac and pulmonary systems, worldwide [1][2][3]. It is estimated that SARI causes approximately 4.2 million deaths annually.…”
Section: Introductionmentioning
confidence: 99%
“…Surveillance indicated higher rates of viral infections among ARI patients, both in the outpatient clinics and inpatient wards, compared with the rates reported from Egypt influenza surveillance during the inter-pandemic phase [ 4 , 16 , 17 ]. This finding reflects the surge of SARS-CoV-2 when first introduced into a naïve population and could indicate high sensitivity of the surveillance.…”
Section: Discussionmentioning
confidence: 86%
“…In Egypt, the number of infants aged 1–11 months hospitalized for moderate or severe lower RTIs was 5135/100,000 for the period 2009–2012, with 40% of patients subsequently diagnosed with bronchiolitis [ 9 ]. A 2015 study on severe acute respiratory illness in Egyptian patients found that the causative organism was influenza A in almost half of cases, influenza B in 25% and respiratory syncytial virus in another 25%, with 35.3% of patients being children under 5 years of age [ 10 ].…”
Section: Introductionmentioning
confidence: 99%